The American party system and the American people - Greenstein, Fred I. (Englewood Cliffs, N.J. : Prentice-Hall, 1963)
The book is centered on what the party system do for America and the effects of party politics to the well being of the American citizenry.
Includes bibliographical references.
sju 23/01/2019
Loans
Keywords: Political parties; United States